2015
DOI: 10.1016/j.orl.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Sequential scheduling on identical machines

Abstract: We study a sequential version of the well-known KP-model: Each of n agents has a job that needs to be processed on any of m machines. Agents sequentially select a machine for processing their jobs. The goal of each agent is to minimize the finish time of his machine. We study the corresponding sequential price of anarchy for m identical machines under arbitrary and LPT orders, and suggest insights into the case of two unrelated machines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…[15] for a network routing counterexample where the sequential price of anarchy is unbounded, while the price of anarchy is known to be 5/2 [5,14]. Indeed, subsequent to [29], for a handful of problems it was shown that the sequential price of anarchy is lower than the price of anarchy [18,20,21,29], while for some others this is exactly opposite [2,9,15].…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…[15] for a network routing counterexample where the sequential price of anarchy is unbounded, while the price of anarchy is known to be 5/2 [5,14]. Indeed, subsequent to [29], for a handful of problems it was shown that the sequential price of anarchy is lower than the price of anarchy [18,20,21,29], while for some others this is exactly opposite [2,9,15].…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…For example, while the PoA is unbounded for the Unrelated Machine Scheduling game, they showed that its SPoA is bounded. In fact, positive results showing that the SPoA presents lower values than the PoA has been displayed for various games ( [5,7,8,9]). However, that is not always the case ( [10,11,12]), and we show that sequential transportation games fall in this category for all social cost functions analyzed in this paper.…”
Section: Introductionmentioning
confidence: 98%
“…• Hassin and Yovel [23] consider machine scheduling and focus on the special case of related machines. The authors prove that for this model, the SPoA is at most 2 while the PoA is Θ(ln n/ ln ln n).…”
Section: Introductionmentioning
confidence: 99%